2009
DOI: 10.1038/ajg.2009.254
|View full text |Cite
|
Sign up to set email alerts
|

EUS-Guided Biliary Drainage With One-Step Placement of a Fully Covered Metal Stent for Malignant Biliary Obstruction: A Prospective Feasibility Study

Abstract: EUSBD with one-step placement of an FCSEMS may be feasible, safe, and effective as an alternative to PTBD in cases of malignant biliary obstruction when ERCP is unsuccessful. Prospective randomized trials of EUSBD with plastic stent vs. EUSBD with FCSEMS may be needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
149
0
4

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 171 publications
(155 citation statements)
references
References 24 publications
2
149
0
4
Order By: Relevance
“…biliary drainage (EUS-BD) has been increasingly reported in patients who underwent failed endoscopic transpapillary biliary drainage [2][3][4]. There are two main approach routes in EUS-BD: endoscopic ultrasound-guided choledochoduodenostomy (EUS-CDS) and endoscopic ultrasoundguided hepaticogastrostomy (EUS-HGS).…”
mentioning
confidence: 99%
“…biliary drainage (EUS-BD) has been increasingly reported in patients who underwent failed endoscopic transpapillary biliary drainage [2][3][4]. There are two main approach routes in EUS-BD: endoscopic ultrasound-guided choledochoduodenostomy (EUS-CDS) and endoscopic ultrasoundguided hepaticogastrostomy (EUS-HGS).…”
mentioning
confidence: 99%
“…[12][13][14][15][16] Endoscopic drainage of pancreatic pseudocysts has become an accepted alternative to surgery when intervention is indicated. 6 The advantages of endoscopic drainage compared to percutaneous drainage include the ability to place multiple internal drains through one puncture site and the avoidance of development of a pancreaticocutaneous fistula in pseudocysts that communicate with the pancreatic duct.…”
Section: Discussionmentioning
confidence: 99%
“…In a report by Bories et al (7), including 10 cases which underwent transenteric ESBD with plastic and covered metal stents, biloma and cholangitis caused by stent migration or shorting occurred in 2 of 3 patients who had undergone one-step placement of a covered SEMS. Recently, Park et al (13,14) reported one-step placement of a fully-covered SEMS via the stomach or duodenum to the intra/extra-hepatic bile duct. There were no complications such as bile leakage and stent migration.…”
Section: Discussionmentioning
confidence: 99%